The Role of Treatment Supervisors and Family Support in Pulmonary Tuberculosis Patient Recovery: Cross Sectional - Nazaruddin, Nazaruddin; Yusnayanti, Cici; Purnamasari, Anisa; Lisnawati, Lisnawati (PT. Nursing Genius Care, 2026)
Background: Pulmonary tuberculosis is an infectious disease that requires effective treatment supervision and support from the immediate environment to achieve recovery. The role of Treatment Supervisors and family support are essential components in the success of pulmonary tuberculosis therapy, particularly in primary health care settings. Purpose: This study aimed to analyze the relationship between the role of Treatment Supervisors and family support with the recovery of pulmonary tuberculosis patients in the working area of Poasia Primary Health Center. Methods: This study employed a quantitative analytic method with a cross-sectional design. The study population consisted of all pulmonary tuberculosis patients recorded in the Poasia Primary Health Center registry over the past year, totaling 49 patients. A total of 44 respondents were selected using a total sampling technique. Data were collected using structured questionnaires and analyzed using the Chi-square test and Phi test. Results: The results showed a moderate association between the role of Treatment Supervisors and pulmonary tuberculosis patient recovery (p = 0.006). A moderate association was also found between family support and pulmonary tuberculosis patient recovery (p = 0.006). Conclusion: The role of Treatment Supervisors and family support are significantly associated with the recovery of pulmonary tuberculosis patients. Strengthening the involvement of Treatment Supervisors and families should be a priority in community nursing interventions to improve tuberculosis treatment outcomes.